Cetacean diversity around the Mozambique Channel island of Mayotte (Comoros archipelago) - Kiszka, Jeremy; Ersts, Peter J.; Ridoux, Vincent (J. Cetacean Res. Manage., 2023)
The Indian Ocean was designated as a whale sanctuary in 1979. While cetacean research has been conducted throughout the sanctuary, few studies have been conducted to assess the diversity, distribution and abundance of cetaceans inhabiting the waters surrounding the islands in the northern Mozambique Channel. In order to contribute to management and conservation efforts in this area, a series of small boatbased surveys were undertaken around the island of Mayotte from July 2004 to August 2005 to assess the diversity of cetaceans in the lagoon and surrounding waters, i.e. external barrier reef slope, insular slope (200-1,000m) and oceanic (>1,000m) waters. During this period, more than 284 hours were spent at sea on-effort and 17 cetacean species were recorded around Mayotte (n=286 sightings). One mysticete (1 Balaenopterid) and sixteen odontocetes (1 Kogid, 1 Physeterid, 13 Delphinids and 2 Ziphiids) were observed: spinner dolphin, n=118; pantropical spotted dolphin, n=61; Indo-Pacific bottlenose dolphin, n=44; humpback whale, n=37; melon-headed whale, n=5; Blainville’s beaked whale, n=4; Indo-Pacific humpback dolphin, n=4; common bottlenose dolphin, n=2; Risso’s dolphin, n=2; false killer whale, n=2; dwarf sperm whale, n=2; sperm whale, n=1; pygmy killer whale, n=1; short-finned pilot whale, n=1; Fraser’s dolphin, n=1; and Longman’s beaked whale, n=1. In addition to these 17 species recorded during dedicated surveys, two other cetacean species were observed opportunistically and subsequently identified as the Ginkgo-toothed beaked whale and the blue whale. The relatively large diversity of cetaceans around Mayotte is attributed to the wide range of marine habitats, such as coastal, reef-associated and oceanic, within close proximity to one another.